Association of Sociodemographic Factors and Vitamin-D Levels with the Severity of Depressive Symptoms - Ain, Qurat ul; Mansoor, Sawera; Abbas, Nadeem; Zubair, Usama Bin; Baqir, Muhammad; Latif, Tooba (Pakistan Armed Forces Medical Journal, 2023)
Objective: To study the association of sociodemographic factors and Vitamin D levels with the severity of depressive symptoms in patients with depression. Study Design: Cross-sectional study. Place and Duration of Study: Psychiatry Department, Fauji Foundation Hospital, Rawalpindi Pakistan, from May to Nov 2021. Methodology: This study included all the patients diagnosed with depression per ICD 10 criteria by the consultant psychiatrist. Depression was further categorized in severity using Beck’s Depression Inventory. Vitamin D levels were sent to all the patients diagnosed with depression in the laboratory of our hospital. The cut-off score of less than 50nmol/l was taken as low vitamin levels. Results: Out of 103 patients studied, 23(22.3%) had mild, 49(47.6%) had moderate, and 31(30.1%) had severe depression. In severely depressed patients, 19(61.3%) were above 50 years of age, 12(38.7%) had no formal education, and 21(67.7%) had low vitamin D levels. Among mildly depressed patients, 5(21.7%) were above 50 years of age, 2(8.7%) had no formal education,and 17(73.9) had low vitamin D levels. We found that vitamin D levels, age of the patient, and level of education had a statistically significant relationship with the severity of depression, (p-valve less than 0.05). Conclusions: The level of vitamin D, age, and the level of education had a significant association in the target population with the severity of depressive symptoms.